Motivational Drivers of the Private Provision of Public Goods: Evidence From a Large Framed Field Experiment - Johannees Diederich; Timo Goeschl (University of Heidelberg, Department of Economics, 2014)
Disentangling the motivational drivers of individuals is frequently regarded a key step in reconciling theory and empirical evidence on the voluntary provision of public goods. We present results of a large online field experiments with 12,624 contribution choices by members of the Internet-using German population. Subjects are assigned to six treatments targeted at motivations such as altruism, "warm glow", image motivation, or equity concerns. While evidence on treatment effects is mixed, the data point to signicant effects of framing and the sequence of presenting options. Exploiting variations within the highly heterogeneous sample, the results confirm previous results from a subset of the data on sociodemographics and exogenous environmental conditions as determinants of subjects' choices and add additional evidence that females and older subjects are more inclined to give to the public good.
urn:nbn:de:bsz:16-heidok-167229
Keywords: 330; private provision of public goods; online experiment; field experiment; warm glow; social norms; equity field experiment; online experiment